2014
DOI: 10.1590/s1517-83822014000400040
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory response of Haemophilus influenzae biotype aegyptius causing Brazilian Purpuric Fever

Abstract: The Brazilian Purpuric Fever (BPF) is a systemic disease with many clinical features of meningococcal sepsis and is usually preceded by purulent conjunctivitis. The illness is caused by Haemophilus influenza biogroup aegyptius, which was associated exclusively with conjunctivitis. In this work construction of the las gene, hypothetically responsible for this virulence, were fusioned with ermAM cassette in Neisseria meningitidis virulent strains and had its DNA transfer to non BPF H. influenzae strains. The eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…The transcriptional fusion vector pLAN78 was used to evaluate the transformation capacity in Hae. pLAN78 was already successfully transferred to N. meningitidis and Hi strains ( Cury et al, 2014 ). Hae strains were again not competent to transformation whereas 19 and 4 CFU of Hi RdKW20 and Hi β-lac, respectively, were observed.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The transcriptional fusion vector pLAN78 was used to evaluate the transformation capacity in Hae. pLAN78 was already successfully transferred to N. meningitidis and Hi strains ( Cury et al, 2014 ). Hae strains were again not competent to transformation whereas 19 and 4 CFU of Hi RdKW20 and Hi β-lac, respectively, were observed.…”
Section: Resultsmentioning
confidence: 99%
“…Our data showed that las was overexpressed in the Hae_BPF F3033 in the latter stages of the infection. In a previous study, our group showed that the transfer of las in NTHi strains caused a higher production of the tumor necrose factor alpha - TNF-α and interleukin 10 - IL10 in Hec1b versus the wildtype strains ( Cury et al , 2014 ). The las gene in Hae ( lav in non-BPF H. influenzae ) is evolutionarily related to the AT autB prone to phase variation in N. meningitidis ( Davis et al , 2001 ) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was hypothesized that acquisition and/or expression of particular virulence factors led to the emergence of BPF strains (3, 4), but the exact mechanism(s) behind the transition from causing conjunctivitis to causing severe invasive disease was never elucidated. However, a number of Haemophilus influenzae biogroup aegyptius -specific virulence factors have been identified and studied (5), such as lipooligosaccharide structure (1), extracellular proteins (6), and outer membrane proteins/adhesins (4, 7). Nevertheless, no factors were conclusively shown to be completely necessary for virulence (1), in part due to a lack of high-quality genome sequences.…”
Section: Announcementmentioning
confidence: 99%